Clay‐Graphene Nanoplatelets Functional Conducting Composites. (29th August 2016) - Ruiz‐Hitzky, Eduardo; Sobral, Maria Madalena C.; Gómez‐Avilés, Almudena; Nunes, Claudia; Ruiz‐García, Cristina; Ferreira, Paula; Aranda, Pilar
Abstract : An approach to functionalize graphene‐based materials has been developed by assembling graphene nanoplatelets (GNP) with clay minerals. Under convenient sonomechanical treatment, clay–GNP mixtures may produce very stable water dispersions in particular using sepiolite fibrous clay. While in the absence of clay a rapid decantation of GNP in water is observed, in the presence of sepiolite the resulting dispersions remain stable during months without syneresis effects. Rigid but flexible self‐supported films are easily obtained by filtering of these dispersions. As the electrical percolation threshold corresponds to sepiolite/GNP composites of 0.5:1 in weight, doping these systems with multiwalled carbon nanotubes (MWCNTs) significantly enhances their electrical conductivity. The particular microporosity of the sepiolite component allows interactions with molecules, such as organic dyes, as well as polymers, such as biopolymers, opening the way to functional materials for advanced applications due to their inherent conductivity afforded by the GNP and MWCNTs carbonaceous components. In fact, using very small amount of MWCNT together with GNP can obtain composites with significant electrical conductivity, maintaining the enhanced mechanical properties, at a lower cost. Abstract : Graphene‐based composites are prepared by assembling graphene nanoplatelets with clay minerals using sonomechanical treatment. Sepiolite fibrous clay produces very stable water dispersions even for low clay content giving rise to homogenous composites at the nano/microscale. The process allows incorporation of other components such as multiwalled carbon nanotubes, molecular dyes, and polymers, giving rise to functional materials showing enhanced electrical conductivity and other predesigned properties.